ChemInform Abstract: Azine and Diazine Functionalization Using 2, 2, 6, 6‐Tetramethylpiperidino‐Based Lithium—Metal Combinations: Application to the Synthesis of 5, 9‐Disubstituted Pyrido[3′, 2′:4, 5]pyrrolo[1, 2‐c]pyrimidines. Issue 18 (April 2016) - Marquise, Nada; Nguyen, Tan Tai; Chevallier, Floris; Picot, Laurent; Thiery, Valerie; Lozach, Olivier; Bach, Stephane; Ruchaud, Sandrine; Mongin, Florence
Abstract: The title compounds show moderate antiproliferative activity and low kinase inhibition in melanoma cells.